The legal basis for the processing of athlete’s personal data by the World Anti-Doping Agency and its signatories under the General Data Protection Regulation - Rieba, Liene Lelde (Riga Graduate School of Law, 2021)
Professional athletes have to provide different types of data daily. These data include a special category of data supplied to the national anti-doping organizations and other sport governing bodies. The purpose of such extensive data collection is to ensure fair, transparent, and equal competition. The processing of personal data is based primarily on the athlete’s consent, which may not be freely given in all circumstances. The primary purpose of the master thesis is, therefore, to examine the appropriate legal basis for the processing of athlete’s data and in establishing what would be the most appropriate basis for the processing of athlete’s personal data, including with respect to the special categories of data processed by anti-doping organizations and, based on these findings, propose amendments to the Latvian National Anti-Doping Regulation. Research shows that consent cannot be used as a valid legal basis for the lawful processing of athlete’s data, as it is not freely given, informed, and athletes may experience negative consequences if the athlete does not consent. The more appropriate legal basis for the data processing would be to establish processing based on the controller’s legal obligations. However, in order to have a legitimate ground, a legal obligation would need to have support in the EU or national laws or regulations, which is rarely the case, casting a shadow of doubt over the legitimacy of the processing of athlete’s personal data. In the case of a special category of data, substantial public interest can be relied on as the legitimate legal basis for data processing
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law; Data protection; Sports law